Nutritive Quality of β-Mannanase Treated Copra Meal in Broiler Diets and Effectiveness on Some Fecal Bacteria - Khanongnuch, Chartchai; Sa-nguansook, Chatchai; Lumyong, Saisamorn (International Journal of Poultry Science, 2006)
The copra meal (CM) was hydrolyzed to prepare the enzymatic treated CM (ETCM) by bacterial β-mannanase. The ETCM showed markedly reduction in crude fiber about 14%, while an ether extract, nitrogen-free extract and metabolizable energy value were increased approximately 10%, 4.7% and 16.5%, respectively, compared to non-enzymatic treated CM (NTCM). The digestibility of ETCM nutrient components were also increased, especially, in case of fiber which was increased from 45.35% to 71.98%. The effect on body weight gain of broiler fed with 15% and 20% (w/w) ETCM was not significantly different (P>0.05) in all treatments. Feed consumption decreased (P< 0.05) when fed the diets containing ETCM and NTCM, but feed conversion ratio (FCR) was improved significantly (P< 0.05), especially at the level of 20% ETCM which the FCR value 2.06 was obtained compare to 2.12 of NTCM group. In addition, the number of E. coli and Salmonellae count in broiler feces were also decreased significantly when fed with ETCM diets.